Renal dysfunction is associated with higher central venous pressures in patients with Fontan circulation. (5th August 2018) - Broda, Christopher R.; Sriraman, Hamsini; Wadhwa, Devanshi; Wang, Yunfei; Tunuguntla, Hari; Akcan‐Arikan, Ayse; Ermis, Peter R.; Price, Jack F.
Abstract: Purpose: Elevated central venous pressure (CVP) has deleterious effects on several organ systems in patients with Fontan circulation. However, the relationship between CVP and estimated glomerular filtration rate (eGFR) has not been assessed in patients with Fontan circulation. Methods: Patients with Fontan circulation whose hemodynamics were assessed by catheterization between 1987 and 2015 and had a serum creatinine measured within 72 hours prior to the procedure were included for analysis. Patients with primary kidney disease were excluded. Renal function was calculated by "bedside Schwartz" equation in children (< 18 years) and Modification of Diet in Renal Disease equation in adults. Renal dysfunction (RD) was defined by eGFR < 90mL/min/1.73m 2 . Fontan patients with and without RD were compared based on demographics, co‐morbidities, medication use, echocardiographic findings, hemodynamics assessed at time of catheterization, and laboratory testing values. Results: Sixty‐seven patients with Fontan circulation met inclusion criteria and 15 patients (22%) had RD; eGFR (mL/min/1.73m 2 ) was 60–89in 13 (87%), 45–59in 1 (7%), and 30–45in 1 (7%). Compared to patients with eGFR equal to or greater than 90, patients with RD had higher CVP (18.0 [15.0–21.0] mm Hg vs 13.5 [12.3–16.0] mm Hg ( P = 0.001), lower pulmonary blood flow 2.2 [1.9–2.6] L/min/m 2 vs 2.8 [2.3–3.7] L/min/m 2, higher ventricular end‐diastolic pressure 10.5 [7.0–17.3] mm Hg vs 8.0 [6.0–10.0] mm Hg ( P = 0.050), were more likely to have worse atrioventricular valve regurgitation ( P = 0.02) and were more likely to be African American ( P = 0.009). Conclusions: In this study population, renal dysfunction in patients with Fontan circulation is associated with increased CVP and factors that affect CVP. African Americans with Fontan circulation may be at particular risk for renal dysfunction. Continued investigation of the effects of venous congestion on kidneys and other factors associated with renal dysfunction in patients with Fontan circulation is warranted.